Financial Statement Analysis Training for the Management of Rukun Palembang Cooperative - Soejono, Fransiska; Kusmawati, Kusmawati; Nicholas, Nicholas; Thimothy, Thimothy (Penerbit Goodwood, 2023)
Purpose: The management of the cooperative must to know about soundness of their cooperative to plan and decision making in enhancing the welfare for its members. So, the purpose of this activity are to explain for management of Rukun credit cooperative how to analyze financial statement to know about soundness rate of their cooperative. Information about soundness rate can be basic to financial management of Rukun credit cooperative. Methodology: This activity was carried out at the Shop House (Ruko) Kopdit Rukun Jl. Siaran Perumnas Sako. The participants of the activity are Managers and Administrators of Kopdit Rukun. Activities are carried out in the form of lectures, questions and answers, discussions and practices of calculating and analyzing financial statements. Giving lectures using the help of projectors, laprop, screens, whiteboards, markers, stationery, paper and also cooperative annual report books. Activities were evaluated using hardfile questionnaires distributed at the beginning and end of activities containing pre and post tests. The total participants were 28 people and the response rate to the pre and post test questionnaire was 85.71% (24 out of 28 participants). Results: Based on the results of the pre and post test questionnaire, an increase in understanding was obtained which was seen from the number of correct answers increased from 61.218% to 66.346%. The number of trainees from the beginning of the activity to its completion shows more than 80% and this means that this activity is in demand by participants. Based on the number of correct answers from 24 participants, it was found that 12 (50%) participants experienced an increase in understanding, 8 (33%) participants experienced a decrease in understanding, and 4 (17%) other participants did not experience a change in understanding. Limitation: The number of trainees from the beginning of the activity to its completion shows more than 80% and this means that this activity is in demand by participants. Contribution: The results of the questionnaire on material understanding by comparing answers before and after the training showed an increase in scores, and this means that participants' understanding of financial statements and financial statement analysis has increased.